Nucleotides in neuroregeneration and neuroprotection. (May 2016) - Miras-Portugal, M. Teresa; Gomez-Villafuertes, Rosa; Gualix, Javier; Diaz-Hernandez, Juan Ignacio; Artalejo, Antonio R.; Ortega, Felipe; Delicado, Esmerilda G.; Perez-Sen, Raquel
Abstract: Brain injury generates the release of a multitude of factors including extracellular nucleotides, which exhibit bi-functional properties and contribute to both detrimental actions in the acute phase and also protective and reparative actions in the later recovery phase to allow neuroregeneration. A promising strategy toward restoration of neuronal function is based on activation of endogenous adult neural stem/progenitor cells. The implication of purinergic signaling in stem cell biology, including regulation of proliferation, differentiation, and cell death has become evident in the last decade. In this regard, current strategies of acute transplantation of ependymal stem/progenitor cells after spinal cord injury restore altered expression of P2X4 and P2X7 receptors and improve functional locomotor recovery. The expression of both receptors is transcriptionally regulated by Sp1 factor, which plays a key role in the startup of the transcription machinery to induce regeneration-associated genes expression. Finally, general signaling pathways triggered by nucleotide receptors in neuronal populations converge on several intracellular kinases, such as PI3K/Akt, GSK3 and ERK1, 2, as well as the Nrf-2/heme oxigenase-1 axis, which specifically link them to neuroprotection. In this regard, regulation of dual specificity protein phosphatases can become novel mechanism of actions for nucleotide receptors that associate them to cell homeostasis regulation. This article is part of the Special Issue entitled 'Purines in Neurodegeneration and Neuroregeneration'. Highlights: Spinal cord trauma increases the expression of P2X4 and P2X7 receptors around the damage. Locomotor effect of spinal cord contusion can be reversed by acute transplantation of ependymal progenitor cells expressing P2X-P2Y receptors. Sp1 functions as a scaffolding protein to recruit additional nuclear factors that elicit the expression of regeneration-associated genes. Nucleotide receptors promote neuroprotection by modulation of GSK3, Nrf-2/HO-1 and ERK1, 2 signaling cascades. P2Y13 receptors target dual specificity protein phosphatase DUSP2 to regulate MAPK signaling homeostasis.